Manajemen pada Unit Mutu Pelayanan Medik di Rumah Sakit Jiwa Grhasia - Ari Setiawan (Universitas Ahmad Dahlan, 2020)
Medical services aim to ensure optimal successful healing of clinical symptoms experienced by patients. The medical services provided should be in accordance with applicable regulations and must also be accountable in accordance with the standards of each profession. The quality of the medical services provided depends on the efforts of the doctor/specialist in maintaining their expertise as much as possible. In maintaining quality, professional quality review and control efforts are carried out. Purpose: This study aims to understand the description of human resource input, management functions in the medical development unit, and the description of service output in the medical development unit. Methods: This research is qualitative research with The data collection methods used were observation and interviews. Observations were carried out by observing every activity at the Grhasia Yogyakarta Mental Hospital, especially in the Medical Service Quality Unit. Results: the human resources input section does not meet the criteria for field graduates, the budget is sufficient, service standards are always updated, the management process is integrated with other units, and service quality is improved as an output of quality management. Conclusion: The medical service quality management process and management output have gone well according to plan, while management resource input needs to continue to improve the quality of human resources.